THE JOHANSEN-JUSELIUS MULTIVARIATE COINTEGRATION TECHNIQUE: APPLICATION AND INTERPRETATION - NKORO, EMEKA; UKO, AHAM KELVIN (Advances in Social Sciences Research Journal, 2016)
Cointegration is the simplest way of detrending series whose mean, variance as well as autocorrelation functions changes over time due to the presence of unit roots. However, the issue has shifted to the application of the appropriate cointegration technique as various cointegration techniques abound. Hence, this study reviews the issues surrounding the application and interpretation cointegration techniques within the context of Johansen-Juselius multivariate cointegration framework. The study shows that the adoption of the Johansen-Juselius multivariate cointegration technique rests on the pretests for unit roots. The study reveals that Johansen-Juselius multivariate cointegration technique is preferable when dealing with more than two variables that are integrated of the same and as well different order, I(d) .However, the Johansen-Juselius multivariate cointegration technique is robust when dealing with variables of the same order of integration. The number of cointegrating vectors is detected through the two likelihood ratio test statistics (trace and maximum test). Although the major difficulty lies in the identification of the cointegrating vectors where there are multiple cointegrating vectors. In this approach, cointegration is said to be established when there is at least one cointegrating vector. Based on forecast and policy implications, this paper explores the conditions that necessitate the application of the Johansen and Juselius cointegration technique. This is to avoid its wrongful application, which may in turn lead to model misspecification, inconsistent and unrealistic estimates. However, this paper cannot claim to have treated the underlying issues in their greatest details, but have endeavoured to provide sufficient insight into the issues surrounding Johansen and Juselius cointegration technique to practitioners to enable them apply and interpret and also, follow discussions of the issues in some more advanced texts.